STUDY THE RELATIONSHIP BETWEEN USE OF ICT AND ACADEMIC ACHIEVEMENT OF STUDENTS AT UNIVERSITY LEVEL IN PANDEMIC 2020 - Afshan Sharif; Dr. Sohaib Sultan; Dr. Sadaf Zamir Ahmed; Dr. Rabia Mushtaq; Huma Akbar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
In the twenty-first century, technology is a major concern in all fields, including education. ICT plays its major role in education during the COVID-19 epidemic. Due to Covid-19, education system was fully transformed into ICT based learning. The purpose of current investigation is to determine relationship between the use of ICT and academic achievement of students at university level in pandemic 2020. Investigation of the study based on the objectives to examine the attitude of students regarding usage of the ICT at university level in pandemic 2020; to determine the effects of demographic factors (Qualification, Gender, Age) over the use of ICT and academic achievement of students at university level in pandemic 2020. The Population of this investigation consisted of all the university students of Islamabad. The sample of this study was 140 students from all the universities of Islamabad. In order to collect the data simple random sampling was used in this study. The design of the study was descriptive research design and it was a quantitative study. A self-made instrument was used in order to gather data. The instrument having 10 items was a close-ended questionnaire. The statistical techniques used were Frequency, Percentage, Mean, t-test, ANOVA and Pearson Corelation. It was concluded that there was a positive and encouraging attitude of students about the use of ICT at university level in pandemic 2020, which is important for students for their academic achievement. The second conclusion is based on second objective and it is concluded that there is a significant effect of demographic factors (gender, age, qualification) over the perception of students regarding the ICT usage in Academic Achievement. The third conclusion is based on third objective and it is concluded that there is no significant relationship between the use of ICT and academic achievement of the students. There is a positive correlation between use of ICT and Academic Achievement of the students.